2021
DOI: 10.20473/ijtid.v9i1.22609
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Covid-19 Confirmed Died Patients in Dr. Kariadi Hospital: A Retrospective Study

Abstract: Covid-19 is a communicable disease causing global pandemic. Some factors inflict worse infection. This study aims to investigate risk factors of Covid-19 confirmed died patients at Dr. Kariadi Hospital Semarang. It is a retrospective study with a total sample of all Covid-19 confirmed patients involving died and healed patients from March to June 2020. Data was gathered from screening forms and analysed with Chi Square (confidence interval of 95%). This study found sixteen risk factors of Covid-19 confirmed di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
1
4
0
1
Order By: Relevance
“…Our data suggested that the patients who died were significantly older than those who recovered (Table 2). This aligns with previous studies, reporting that younger patients had a higher likelihood of surviving COVID-19 [19][20][21]. Older age has consistently emerged as a robust independent predictor of mortality among COVID-19 patients [22][23][24].…”
Section: Short Communication Original Articlesupporting
confidence: 91%
“…Our data suggested that the patients who died were significantly older than those who recovered (Table 2). This aligns with previous studies, reporting that younger patients had a higher likelihood of surviving COVID-19 [19][20][21]. Older age has consistently emerged as a robust independent predictor of mortality among COVID-19 patients [22][23][24].…”
Section: Short Communication Original Articlesupporting
confidence: 91%
“…Leaflets prepared in local languages should be administered and health professionals should provide detailed information about COVID-19 to their patients. [45][46][47] CONCLUSION Some respondents had a low knowledge category (54 of 116), and the most positive perception category (57 of 116). Respondents with high and very high levels of knowledge were 48 of 116.…”
Section: Understanding Of the Covid-19 Virusmentioning
confidence: 99%
“…Data indicate Covid-19 is more prevalent among the elderly and those with comorbidities. The mortality rate is higher among older people [5].…”
Section: Introductionmentioning
confidence: 98%